Juridical Analysis of Divorce Annulment Norms Reviewed from Law Number 23 of 2006 concerning Population Administration (Comparative Study with Australia) - Roni Eko Susanto; I Wayan Putu Sucana Aryana; Cokorde Istri Dian Laksmi Dewi (Jurnal Indonesia Sosial Sains, 2024)
Marriage is a physically and mentally binding agreement based on faith, so marriage is living with a man and a woman by fulfilling certain conditions. There are times when disputes are involved in a marriage between husband and wife, which, if not managed properly, can cause divorce. It is regulated regarding the annulment of divorce as contained in Law Number 23 of 2006. However, the mechanism for the annulment of divorce is not further regulated in Indonesian law, so it is necessary to discuss the current arrangement and its comparison with Australia and analyze the existence of divorce annulment arrangements in Indonesia. This type of research is normative research using primary, secondary, and tertiary legal materials, a statutory approach, and a comparative study comparing with other countries, namely Australia, using a conceptual approach and a case approach. Nothing related to the mechanism for annulment of divorce was found in Indonesia except in the KHI, while in Australia, it can be found in the Family Law Act 1975. Therefore, in Indonesia, further arrangements are needed in the form of legislation.